Software based in digital proscesing of tophographics data base, to calculate levels of RSSI on BTS of telephony cellular - Díaz Zegarra, José Alberto (2005)
A software was implemented in visual environment that carries out the analysis of covering of a BTS of cellular telephony, starting from parameters provided by the maker of the antenna and of the digital data corresponding to the topography of the place. The implemented software has graphic interfaces to enter the parameters of the antenna, radiation pattern, etc. and coordinated of the location. The program presents a visual report of the covering by means of a code of colors, indicating the different reception levels and the report on the obtained data of the calculation of covering of a station bases, using mathematical models for systems outdoor. The data for the validation of the present work were obtained of the implementation of a station it bases cellular of tests, consistent in a transmitter of cellular telephony in the band of 800 MHz, sectoral antenna, was carried out the mensuration of the received levels RSSI and these they are compared with the theoretical ones and then they are drowed in Matlab to determine the absolute error among the real values and those obtained by means of the software.